Pengaruh Store Atmosphere dan Life Style terhadap Keputusan Pembelian : Survei pada Konsumen Coffee Shop Parewa - Dita Aulia; Muhammad Tegar Irsyad (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The purpose of this study is to analyze the effects of store atmosphere and customer lifestyle on purchasing behavior, focusing specifically on Parewa customers. Employing a quantitative survey methodology, the research integrates an explanatory approach with a correlational design to explore the relationships between these variables. The study follows a cross-sectional framework, with data collected at a single point in time. The individual purchaser serves as the unit of analysis, and the research is carried out within a natural, real-world environment. The findings demonstrate a statistically significant and positive correlation between store atmosphere and customers' purchasing decisions. This implies that an inviting and comfortable store environment increases the likelihood of customer purchases at Parewa. Additionally, the results show a significant positive correlation between lifestyle and purchasing behavior, suggesting that customers with enhanced lifestyles are more inclined to purchase Parewa products. These insights underline the importance of aligning store ambiance and customer lifestyle preferences to drive sales effectively.